CHANGES OF COLOR AND P-KAROTEN RATE IN THE UBI.JALAR (IPOMEA BATATAS, L) FLOWS BLEACHING - Regina Tutik Padmaningrum; M. Pranjoto Utomo (Jurnal Penelitian Saintek, 2007)
he researh to stuJlythe influence of the kinds and the concentrations of bleach solution to the co1lientof fJharoten and the color ofjaw a sweet potato flour has been done. Yellowjawa sweet potato was used in this reseach. This reseon:h was a descripstive qualitative research. The subject of the researdt was jawa sweet potato and the object was jawa sweet potato flourquantities  including the content of fi-charotenand the color of theflour.. TIre independen: variables were the kinds .and the concentrations of bleach solution. and the dependent variableswere the con/ell!offJ-charoten ami.the color ofjawa sweet potato flour. In  1.00% bleach solllliDn. the costen:  of fi-charoten  with sodium sulfite,  sodium  bisulfite.  Co(OHJ!l.   ascorbic  acid  were: 2.18985,1.40835, 2.25795 and 0.78315 mgllOO grams flour  respectively. In1.00% bleach solution. the color of soaked jawa sweet potato flour  in sodium sulfite, sodium bisulfite,. Ca(OH);]ascorbic acid were: red (R= 0.3) =yellow (Y = 0.7). red (R = O.2)-yeJlow (Y = 0.5), red (R = 0.5)-yellow(Y=   1.0)andred(R=0.1)-yeHow(R     = 1.2) respectively. Theresearch showed that the concentration of bleach solution influencedsignificantly the content of fJ-cIwroten and the color of jawa  sweet potato flour. The concentration ofbead: solution tat yielded the bigest content offJ-charotenwas LOW"".